Peran Self Control Pada E-Money dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa di Solo Raya - Putri, Reyzika Rahma; Widarno, Bambang (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of e-money and financial literacy on consumer behavior with self-control as a moderating variable. The population in this study were students studying at universities in Solo Raya. The data in this study were students who used e-money. The sample of this study was 398 samples obtained from 145,676 students from universities in Solo Raya with a purposive sampling method and tested with SPSS software. The data collection method used was a questionnaire. The data analysis methods used were descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests and moderation regression analysis tests. The results of the regression test showed that e-money and financial literacy had a positive and significant influence on consumer behavior. However, self-control, which was initially hypothesized as a moderating variable, did not moderate.